Proposal Rural Development Programme III: 1993-1995 - BRAC (© BRAC, 2016)
1. Executive summary 2. RDP II: achievements to date 3. RDP III : overview of the proposal 4. Village level activities 5. Training and staff development 6. Programme support and management services 7. Programme budget 8. Programme management 9. Related issues 10.Budget